2018
DOI: 10.3389/fpsyg.2018.02243
|View full text |Cite
|
Sign up to set email alerts
|

Heroic Helping: The Effects of Priming Superhero Images on Prosociality

Abstract: Two experiments examined how exposure to superhero images influences both prosociality and meaning in life. In Experiment 1 (N = 246) exposed individuals to scenes with superhero images or neutral images. Individuals primed with superhero images reported greater helping intentions relative to the control group, which, in turn, were associated with increased meaning in life (indirect effect only; no direct effect). In Experiment 2 (N = 123), individuals exposed to a superhero poster helped an experimenter in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Of importance, we do not expect that the obtained effects are unique to children. Other human and nonhuman social categories may elicit broad prosocial motivations and behaviors, including groups that are viewed as deserving of help (e.g., the elderly, victims) and groups that are themselves associated with prosocial behavior (e.g., nurses, superheroes; Aarts et al, 2005;Van Tongeren et al, 2018). We chose to examine the effects of child salience not because they are the only category to elicit such effects but because the social cognitive effects of this category have the potential for high global relevance, and these effects may be underestimated in their pervasiveness and potential impact.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, we do not expect that the obtained effects are unique to children. Other human and nonhuman social categories may elicit broad prosocial motivations and behaviors, including groups that are viewed as deserving of help (e.g., the elderly, victims) and groups that are themselves associated with prosocial behavior (e.g., nurses, superheroes; Aarts et al, 2005;Van Tongeren et al, 2018). We chose to examine the effects of child salience not because they are the only category to elicit such effects but because the social cognitive effects of this category have the potential for high global relevance, and these effects may be underestimated in their pervasiveness and potential impact.…”
Section: Discussionmentioning
confidence: 99%
“…Heroism is a mental construction or schema (Allison & Goethals, 2013), which fulfils basic human needs (Franco et al, 2018). Heroes serve a purpose at intrapersonal, interpersonal, and cultural levels, for example by influencing people to act in prosocial ways and by exhibiting exemplary moral behavior (Van Tongeren et al, 2018). In a study of lay perceptions of the social and psychological role of heroes, Kinsella et al (2015) found that heroes fulfil three primary functions of "enhancing", "moral modeling", and "protecting."…”
Section: Heroismmentioning
confidence: 99%
“…In some cases, they are extolled as moral exemplars who protect and save those in need (Kinsella, Ritchie, and Igou 2015a). Psychology research suggests that heroic behavior can arouse positive emotions such as elevation, gratitude, and admiration (e.g., Algoe and Haidt 2009), and can inspire people to take prosocial or altruistic action (e.g., Van Tongeren et al 2018). Inspiring narratives about heroes' sacrifices and saving others in need can instill hope, improve morale, and motivate people to transcend difficult situations (Kinsella, Ritchie, and Igou 2015b).…”
Section: Chinese Media's Framing Tactics During the Covid-19 Pandemicmentioning
confidence: 99%